Oscillation criteria for nonlinear fractional differential equation with damping term - Bayram, Mustafa; Adiguzel, Hakan; Secer, Aydin (SCIENDO, 2016)
In this paper, we study the oscillation of solutions to a non-linear fractional differential equation with damping term. The fractional derivative is defined in the sense of the modified Riemann-Liouville derivative. By using a variable transformation, a generalized Riccati transformation, inequalities, and integration average technique we establish new oscillation criteria for the fractional differential equation. Several illustrative examples are also given.
Keywords: oscillation; oscillation criteria; fractional derivative; modified Riemann-Lioville derivative; damping term; BOUNDARY-VALUE PROBLEM; POSITIVE SOLUTIONS; EXISTENCE; STABILITY; Physics